Study the Antioxiative Properties of the Marine Algae Cystoseira trinodis extracts from Chabahar Coastal Water - Ali Taheri; Mostafa Ghaffari; Narges sadat Bagherpour; Gilan Attaran Fariman (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2017)
Introduction: Marine macro algae used in pharmaceutical, medical, food, cosmetics and health. Bioactive compounds in seaweeds have widespread the effects of antibacterial, antitumor, antifungal, antioxidant and anticancer. In this study, the antioxidant properties of the extracts of Cystoseira trinodis collected from the Chabahar Bay were studied. Methods: In this experimental study, methanol, chloroform, ethyl acetate and n-hexane extracts of Cystoseira trinodis were prepared. To evaluate the antioxidant properties of algal extracts, the methods of free radical scavenging DPPH, metal chelating activity and ferric reducing activity were used. One way ANOVA and Tukey Posthoc tests were used as statistical analysis by Graphpad-Prism 6 software. Results: The results showed that the highest antioxidant capacity based on the DPPH test for C. trinodis were respectively for ethyl acetate extract (92±4.96% inhibition), in metal ions chelating activity test, the findings were 60.92±0.31% for the ethyl acetate extract, and in ferric reducing activity test, and the chloroform extract absorbance was 0.885±0.03 in 1 mg/ml concentration. Conclusion: This study shows that the different algal extracts of C. trinodis has antioxidant properties with varying degrees and effective use of this compound as a therapeutic tool can be programmed. Further research on the purification and extraction of the constituents of the extract and identification the most effective combination should be conducted.